2023
DOI: 10.1101/2023.04.10.23288389
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The analysis of risk factors associated with multimorbidity of anaemia, malaria, and malnutrition among children aged 6- 59 months in Nigeria

Abstract: In the last ten years multimorbidity in children under the age of five years has becoming an emerging health issue in developing countries. The absence of a proper understanding of the causes, risk factors, and prevention of these new health disorders (multimorbidity) in children is a significant cause for concern, if the sustainable development goal 3 of ensuring healthy lives and the promotion of well-being for all especially in the associated aim of ending preventable deaths of new-borns and children must b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Multimorbidity of anemia, malaria, and malnutrition (MAMM) is a condition in which an individual has two or more of these health outcomes, and is becoming an emergent public health concern in sub-Saharan African countries. A recent study conducted in Nigeria found that one in every two children aged 6-59 months has two or more MAMMs [1]. Similarly, other findings showed that 68.1%, 35.5%, and 43.6% of children aged 6-59 months in Nigeria are anemic [2], malaria positive [3], and malnourished [4], respectively.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Multimorbidity of anemia, malaria, and malnutrition (MAMM) is a condition in which an individual has two or more of these health outcomes, and is becoming an emergent public health concern in sub-Saharan African countries. A recent study conducted in Nigeria found that one in every two children aged 6-59 months has two or more MAMMs [1]. Similarly, other findings showed that 68.1%, 35.5%, and 43.6% of children aged 6-59 months in Nigeria are anemic [2], malaria positive [3], and malnourished [4], respectively.…”
Section: Introductionmentioning
confidence: 88%
“…Meanwhile, in Nigeria, the independent associations of a child's sex, age, and household socioeconomic disparities with a child's independent health and multiple health outcomes have been established in the literature [1,28]. However, the effects of the intersection of these factors have not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation